Case report: High-grade endometrial stromal sarcoma with adrenal glands metastases: An unreported site of metastasis - Zhang, Tao; Feng, Run-lin; Yin, Si-fan; Feng, Wen-bo; Yin, Zhi-yuan; Wang, Hao; Ke, Chang-Xing (Frontiers in Oncology, 2022)
Endometrial stromal sarcoma is a relatively rare malignant tumor that derives from the malignant transformation of primitive uterine mesenchymal cells. It can lead to distant metastases. High-grade endometrial stromal sarcoma is extremely rare. The adrenal glands are an unreported site of metastasis.